Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan (Universitas Negeri Semarang, 2015)
This research aims at knowing the direct and indirect influence of product quality and service quality to customer loyalty through customer satisfaction, and the influence of customer satisfaction to customer loyalty. The population of this research is 5001 customer. Slovin formula is used for obtaining 99 respondents as the sample. Questionnaire adn documentation are metode for collecting the data. In analyzing the data, path analysis is applied. The results of this research show that product quality influences customer loyalty, the service quality influences customer loyalty. Then, customer satisfaction influences customer loyalty; and it mediates the influence of product quality and service quality to customer loyalty. The conclusion of this research is that the higher of customer’s satisfaction will increase the customer loyalty although it may make higher product quality and higher service quality for customer perceived quality.